Role of Isradipine Loaded Solid Lipid Nanoparticles on the Pharmacodynamic Effect in Rats - Thirupathi, G.; Swetha, E.; Narendar, D. (Drug Research, 2017)
Isradipine (ID), is an antihypertensive drug, having low oral bioavailability (15–24%) due to poor aqueous solubility (0.01 mg/mL) and also hepatic first-pass metabolism. Among various approaches, Solid lipid nanoparticles (SLNs) were developed using stearic acid, glyceryl monostearate as lipid matrices for improving the oral bioavailability of ID. ID-SLNs were prepared by using hot homogenization followed by ultrasonication. The prepared SLNs were characterized for size, PDI, zeta potential (ZP), entrapment efficiency (EE) and drug content. In vitro release studies were performed in 0.1NHCl and pH 6.8 phosphate buffer of by open tube method. Physical stability of the SLNs was observed at refrigerated temperature and room temperature for 90 days. Further, pharmacodynamic study was conducted in wistar rats. SLNs prepared with GMS having size of 188.6±3.6 nm, PDI of 0.273±0.052, ZP of − 21.8±2.7 mV with 86.86±0.75% EE were optimized. Differential scanning calorimetric (DSC) study revealed that no interaction between drug and lipid. In vitro release studies showed that more cumulative release of ID in pH 6.8 phosphate buffer than in 0.1NHCl during 24 h. The lyophilized SLN formulation was used in knowing morphology of SLNs, and was found to have spherical shape with increased polydispersity by Scanning electron microscopy. Pharmacodynamic study of SLNs in fructose induced hypertensive rats showed a decrease in systolic blood pressure for 36 h, when compared to suspension, which showed a decrease in systolic blood pressure for only 2 h. Thus, the results conclusively demonstrated the role of SLNs for a significant enhancement in pharmacodynamic effect of ID.